The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3141/2468-06
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclists as Consumers

Abstract: The role of bicyclists as consumers is explored through an examination of the relationship between travel mode and shopping behavior. As cities develop policies to combat congestion and reduce emissions from the transportation sector, tension often develops when scarce road space must be allocated, particularly in dense urban cores. The challenge is to accommodate all travel modes and ensure that local businesses are not negatively affected by infrastructure changes. Previous studies in the United States and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The general consensus is that increases in the number or length of bicycle facilities leads to increased levels of cycling (Dill et al, 2003;Pucher et al, 2010), and thus increased volume of consumers travelling to nearby businesses. In addition, surveys conducted in Portland, Dublin (Ireland), San Francisco, and New York all have found that bicyclists and pedestrians tend to spend more compared to drivers in commercial areas because bicyclists and pedestrians tend to visit local businesses more frequently compared to drivers (Popovich et al, 2014;Bent et al, 2009;Lee, 2008;Clifton et al, 2012). These studies utilized business owner surveys or intercept consumer surveys to learn about the various travel modes by which they arrived at the establishments and resulting expenditure behavior in local businesses.…”
Section: Business Impacts and Economic Vitalitymentioning
confidence: 99%
“…The general consensus is that increases in the number or length of bicycle facilities leads to increased levels of cycling (Dill et al, 2003;Pucher et al, 2010), and thus increased volume of consumers travelling to nearby businesses. In addition, surveys conducted in Portland, Dublin (Ireland), San Francisco, and New York all have found that bicyclists and pedestrians tend to spend more compared to drivers in commercial areas because bicyclists and pedestrians tend to visit local businesses more frequently compared to drivers (Popovich et al, 2014;Bent et al, 2009;Lee, 2008;Clifton et al, 2012). These studies utilized business owner surveys or intercept consumer surveys to learn about the various travel modes by which they arrived at the establishments and resulting expenditure behavior in local businesses.…”
Section: Business Impacts and Economic Vitalitymentioning
confidence: 99%
“…Both San Francisco studies found that those who arrived on foot and those who arrived by bike, taxi, or other (a lumped category) spent less per trip than motorists on average (Bent & Singa, 2009; San Francisco City Transportation Authority, 2010), though neither tested the results statistically. A study from a smaller California city (Davis) found that cyclists spent more on average on downtown retail purchases than motorists (food service, bar, and other service business purchases were excluded), a difference which was marginally significant statistically (p = 0.128) (Popovich & Handy, 2014). The Portland study found that pedestrians spent more on average at bars than motorists, but less at restaurants and convenience stores, and much less at supermarkets.…”
Section: Spending By Travel Modementioning
confidence: 98%
“…Six of the studiestwo in San Francisco, three in Toronto, and one in Victoriawere done via intercept surveys of adult passersby in downtowns or retail corridors of urban areas. One study utilised crosssectional surveys of residents of an entire city, with questions targeted at consumer spending in the downtown area of Davis, California (Popovich & Handy, 2014). Another study used exit surveys of patrons leaving restaurants, bars, and convenience stores across a range of neighbourhood types in Portland, Oregon (Clifton et al, 2013).…”
Section: Spending By Travel Modementioning
confidence: 99%
See 1 more Smart Citation
“…En efecto, el usar la bicicleta regularmente ayuda a reducir las emisiones de carbono, un paso fundamental para combatir la emergencia climática actual (EuropEan Commission, 2017;mizdrak & al., 2020). Además, una mayor presencia de ciclistas puede ayudar a mejorar la cohesión social y la resiliencia de las comunidades (Wild & WoodWard, 2021), y ayudar a disminuir la congestión y mejorar la seguridad vial de las ciudades (marshall & FErEnChak, 2019), colaborando a impulsar las ventas de sectores comerciales de tipo local (VolkEr & handy, 2021;popoViCh & handy, 2014). Finalmente, andar en bicicleta regularmente es una forma de actividad física no intensiva que puede reducir el riesgo cardiovascular y mejorar la salud mental y el bienestar (oja & al., 2021; dE hartog & al., 2010).…”
Section: Introductionunclassified